2014
DOI: 10.1016/j.surfcoat.2014.09.052
|View full text |Cite
|
Sign up to set email alerts
|

A combinatorial comparison of DC and high power impulse magnetron sputtered Cr2AlC

Abstract: Abstract. Using a combinatorial approach, Cr, Al and C have been deposited onto sapphire wafer substrates by High Power Impulse Magnetron Sputtering (HiPIMS) and DC magnetron sputtering. X-ray photoelectron spectroscopy, X-ray absorption spectroscopy and X-ray diffraction were employed to determine the composition and microstructure of the coatings and confirm the presence of the Cr 2 AlC MAX phase within both coatings. One location in both the DCMS and HiPIMS coatings contained only MAX phase Cr 2 AlC.The ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The Cr 2 AlC (103) peak is stronger for 120 V, which can be related to larger grains, higher crystallinity, or more MAX phase. This is in good correlation with the results of Field et al [ 27 ], who showed for DCMS and HiPIMS deposited coatings that Cr 2 AlC (103) reflection was the highest. Furthermore, the coating deposited at 120 V displays the presence of Cr 7 C 3 , AlCr 2 , and Cr 23 C 6 peaks.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The Cr 2 AlC (103) peak is stronger for 120 V, which can be related to larger grains, higher crystallinity, or more MAX phase. This is in good correlation with the results of Field et al [ 27 ], who showed for DCMS and HiPIMS deposited coatings that Cr 2 AlC (103) reflection was the highest. Furthermore, the coating deposited at 120 V displays the presence of Cr 7 C 3 , AlCr 2 , and Cr 23 C 6 peaks.…”
Section: Resultssupporting
confidence: 92%
“…Cr 2 AlC has been produced using magnetron sputtering, either by sputtering from elemental targets [ 26 ] or compound targets [ 23 ]. Field et al [ 27 ] deposited Cr 2 AlC coatings using direct current magnetron sputtering (DCMS) and high power impulse magnetron sputtering (HiPIMS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of all coatings shows that preferential (103) planes grew during the deposition process instead of (110) or (100/101). A dominant (103) diffraction peak has been reported by Zamulaeva et al [45,46] for the Cr 2 AlC coatings deposited on Ti substrates, as well as by Field [47]. In contrast, Li et al [48] discussed preferential coating growth at (110) planes taking place during deposition on the M38G super alloy.…”
Section: Coating Microstructurementioning
confidence: 91%
“…The films exhibited excellent oxidation and corrosion properties. Field et al reported the synthesis of MAX-phase Cr 2 AlC films by a combinatorial approach, especially comparing the HiPIMS and DC magnetron technique under similar conditions on the Cr target [30]. The HiPIMS coating generally exhibited lower resistivity than the conventional DC magnetron sputtering (DCMS) coating.…”
Section: Introductionmentioning
confidence: 99%